Structure and reactivity in neutral organic electron donors derived from 4-dimethylaminopyridine - Garnier, Jean; Kennedy, Alan R.; Berlouis, Leonard E. A.; Turner, Andrew T.; Murphy, John A. (Beilstein Journal of Organic Chemistry, 2010)
The effects on the redox properties of modifying the molecular skeleton of neutral bis-2-(4-dimethylamino)pyridinylidene electron donors, derived from 4-dimethylaminopyridine (4-DMAP), have been explored, by varying two parameters: (i) the length of a polymethylene chain linking the two pyridine-derived rings and (ii) the nature of the nitrogen substituents on the 4 and 4′ positions of the precursor pyridines. Restricting the bridge length to two methylene units significantly altered the redox profile, while changes in the nitrogen-substituents at the 4 and 4′ positions led to only slight changes in the redox potentials.
Keywords: dication; 4-DMAP; electron donor; electron transfer; radical cation; redox; reduction